Radial Sensitivity of the Nuclear Shell Structure at N=92 - Swain, R. R.; Anupam, A.; Mohanty, P.; Jena, K. K.; Agarwalla, S. K.; Sahu, B. B. (Atom Indonesia, 2025)
The nuclear ground-state properties of Sm isotopes are calculated and analyzed using an improved mass formula. The asymmetric energy term is consistently observed, separated into a volume and surface component. While distinctive signatures for certain isotopes remain elusive, the results show reasonable agreement with experimental data and well-established theoretical models such as the Relativistic-Continuum-Hartree-Bogoliubov (RCHB) and the Finite Range Droplet Model (FRDM). By utilizing a root-mean-square (rms) charge radius formula that incorporates both shell and deformation effects, the study provides new insights into the anomalous shifts observed in magic isotopes (N=82, N=126), as well as in N=92, 136, and 144 within the isotopic series of the "Sm" element.